State care services as devices of acceptance to the social body: the case of Afro-descendant migrant mothers in Chile, beneficiaries of the National Child Health Program - Reyes Muñoz, Yafza; Reyes Muñoz, Vania (Frontiers in Human Dynamics, 2024)
Introduction In the field of medical anthropology, particularly from the practices of medical care in a situated context, the text discusses how state care services under the “National Child Health Programme” implemented by nursing professionals in Chile transmit values and expectations that could be transformed into devices of acceptance to the social body for migrant mothers of African descent who come with their children to health centres. Methods The Methodology employed in this study was devised through a case study in the commune of Talca, within the Maule region, utilizing semi-structured interviews with nurses who work within the Programme, as well as open interviews and thematic workshops with migrant women users of the Programme. Results The results point to the valuation of the programme by the women, who identify it as an instance of providing and receiving care for their children; they also recognise that they are judged by their caregivers for not “correctly” following the instructions given to them with their children living in Chile or for exercising transnational maternity. On the other hand, nursing professionals revealed racial and class prejudices about women of African descent, especially Haitian women. Discussion It is suggested that this programme, recognized regionally as an effective assistance and care policy in the fight against infant mortality and morbidity, becomes an acculturation device for migrant mothers and their children born in Chile. It is expected that both mothers and children adhere to the program’s guidelines, resulting in similar behaviours and attitudes as those of Chilean mothers. This generates few instances of learning and appreciation of the native cultures of the new Chilean infants and reveals that categories of differences such as ethno-racial, gender, and migratory status are articulated in the nurses’ health practices, emphasising the mandate to follow the instructions of migrant mothers and their children.